Hubungan Penggunaan Kontrasepsi Pil Oral Kombinasi (POK) dengan Kejadian Obesitas dan Keputihan di Wilayah Puskesmas Simpang IV Sipin Kota Jambi Tahun 2022 - Riyanti, Endang; Lubis, Sunarti; Haryanti, Reni (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
The aim of the research is to determine the relationship between the use of combined oral contraceptive pills (POK) and the incidence of obesity and vaginal discharge in Simpang IV Sipin Community Health Center Area, Jambi City in 2022. This research is a quantitative study using a cross sectional design. This research was conducted in the Simpang IV Sipin Community Health Center working area, Jambi City from 14 to 20 December 2022. The total population was 130 respondents with samples using total sampling techniques. The data analysis technique used was univariate and bivariate analysis. The results of the study is that there is a relationship between contraceptive users and the incidence of obesity and there is no relationship between contraceptive users and the incidence of vaginal discharge in the Simpang IV Sipin Health Center Area, Jambi City in 2022